2020
DOI: 10.1109/access.2019.2962072
|View full text |Cite
|
Sign up to set email alerts
|

Learning From Accidents: Machine Learning for Safety at Railway Stations

Abstract: enables a global research network that addresses the grand challenge of railway infrastructure resilience and advanced sensing in extreme environments (www.risen2rail.eu) [70].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…The occupational accident data used in this study were collected from the database of the safety management system of a large construction company in Korea, for the period from 2015-2020; in total, 963 occupational accident data entries for the construction site were used. Since there are some studies using similar or small data in previous studies for accident analysis and prediction, the number of samples in this study is judged to be sufficient for machine learning [1,39,40]. However, the initial occupational accident dataset included too many factors, as well as over 130 occupational categories, and over 400 assailing materials.…”
Section: Initial Data and Data Descriptionmentioning
confidence: 99%
“…The occupational accident data used in this study were collected from the database of the safety management system of a large construction company in Korea, for the period from 2015-2020; in total, 963 occupational accident data entries for the construction site were used. Since there are some studies using similar or small data in previous studies for accident analysis and prediction, the number of samples in this study is judged to be sufficient for machine learning [1,39,40]. However, the initial occupational accident dataset included too many factors, as well as over 130 occupational categories, and over 400 assailing materials.…”
Section: Initial Data and Data Descriptionmentioning
confidence: 99%
“…They presented that the developed approaches had the error of energy consumption calculation of less than 0.1 kWh and could reduce the energy consumption by 2.84%. Alawad et al [13] applied a decision tree to analyze fatal accidents. Sysyn et al [14] applied the computer vision concept to predict contact fatigue on crossings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of the many applications that have been applied to CNN, in this subsection, we present those that are specifically related to railways. Such studies have been widely reported in the recent literature and use many data sources; they cover management, maintenance, safety and operations [141]. Image-processing approaches for implementing automatic detection have been suggested for monitoring railway infrastructure [128], rail track maintenance [133], railway track inspections and train component inspections [142]- [152] such as the rolling bearings of trains [153].…”
Section: Related Work In Railway Systemsmentioning
confidence: 99%
“…When the prediction is positive and the ground-truth value is also positive, the prediction is called a true positive (TP). Similarly, false positive (FP), true negative (TN) and false negative (FN) values can be calculated [141]. These four values can be presented as a 2×2 contingency table, called confusion matrix, as depicted in Fig.…”
Section: ) the Evaluationmentioning
confidence: 99%